The Return to Kalokagathia: Curating as Leverage in the Ongoing Dialogues between Aesthetics and Ethics - Suzana Milevska (Philosophies, 2020)
This essay argues that curating brought back a kind of leverage that redressed the otherwise imbalanced relationship between aesthetics and ethics. Curating lends out to art its innocent and aspirational belief in such a balance because the ethical concerns in art theory and art criticism have long been toned down while form was prioritized over content. Ever since the curatorial profession created its own niche in the art world—started, for example, in the West, in the late 1960s with curators such as Siegelaub, Szeemann, or Lippard—curating began to mediate this relationship, thus helping to activate the catalyst potential of art without having to compromise its formal aspects. More specifically, this essay explores the ways in which theories and practices of curating brought back to mind the ancient Greek notion of kalokagathia, the intertwinement of aesthetics and ethics and, with it, other ethical responsibilities, principles, and values that art forgot to address while giving privilege to its formal aspects.